Estudo in vitro do comportamento de facetas confeccionadas com artglass e targis quando submetidas à inserção e remoção de grampos circunferenciais em cromo-cobalto - Marchini, Leonardo [UNESP] (2000)
Aiming to investigate in vitro the behavior of esthetic veneers placed in crows and made of the laboratory resins Artglass and Targis when submitted to insertion and removal of circunferential cobalt-chromium clasps, 24 veneer crowns were made (twelve with Artglass (Heraeus Kulzer) and twelve with Targis (Ivoclar Vivadent)), as well as the respective cobalt-chromium clasps. The crowns were then submitted to five thousand cycles of clasps insertion and removal, using a proper device. Using the verification of the force necessary to remove the clasps over the crowns during the experiment, the clasps and crowns mass variation, and the macroscopic inspection of the veneers, one may conclude that the veneers did not show a significant variation of the force required to remove the clasps over the crowns; they show a little amount of abrasion, possible to detect using a visual inspection and they show a little and variable amount of mass loss, less for that made with Artglass (average of 0,002g) and greater for that made with Targis (average of 0,006g)